Two new species of Phyllachora (Phyllachoraceae, Phyllachorales) on bamboo from China - Li, Xiao-Ling; Wu, Su-Rui; Wang, Chun-Li; Feng, Yun-Li; Zhao, Chun-Yan; Chen, Zheng-Qi; Yu, Jin-Feng; Luo, Rui; Promputtha, Itthayakorn; Sun, Da-Feng (Phytotaxa, 2019)
The genus Phyllachora is the largest genus in the family Phyllachoraceae. Phyllachora species are obligate biotrophic fungi with a tropical distribution. During our field surveys in Yunnan province of China, fifteen graminicolous Phyllachora species were collected. Multi-locus phylogenetic analyses of ITS and LSU together with morphological characteristics, two new species, Phyllachora dendrocalami-membranacei sp. nov. on Dendrocalamus membranaceus and P. dendrocalami-hamiltonii sp. nov. on D. hamiltonii are described and illustrated. Phyllachora dendrocalami-membranacei is characterized by its dump-bell to ellipsoidal to ovoid ascospores (15–25 × 5–11 μm) while P. dendrocalami-hamiltoniicola is distinguished by its dump-bell to ellipsoidal ascospores (15–30 × 8–12 μm).